ELASTISITAS EKSPOR NIKEL TERHADAP IPM, DISTRIBUSI PENDAPATAN, DAN TINGKAT KEMISKINAN DI KABUPATEN LUWU TIMUR - Virgianto, Jurliem; Sukadana, I Wayan (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2023)
The area of ??East Luwu Regency is an area with great potential in terms of natural resources and is where a local and multi-national company operates in the mining sector. The linkage of the mining sector must be improved in order to be able to attract upstream sectors (sectors that have backward linkages). The stronger the relationship between the mining sector and other main sectors such as building/construction, the greater its influence on the development of the East Luwu Regency. The purpose of this study was to analyze the elasticity of nickel exports to HDI, income distribution, and poverty levels. The type of data used is qualitative and quantitative and the source of data is secondary data using time series data for 11 years. Methods of data collection by using the method of observation and non-participant. The analytical technique used in this research is descriptive analysis and distribution lag model. The results of this study are (1) the elasticity of demand for nickel exports to the health index and education index in East Luwu district is inelastic (2) the elasticity of demand for nickel exports to per capita GRDP and the Gini Ratio in East Luwu district is inelastic (3) the elasticity of demand for nickel exports to Severity Index, Depth Index and Poverty Percentage in East Luwu Regency are Inelastic.